PERAN OECD (ORGANIZATION FOR ECONOMIC COOPERATION AND DEVELOPMENT) DALAM MENANGANI PENGHINDARAN PAJAK INTERNASIONAL MELALUI NEGARA TAX HAVEN YAITU KEPULAUAN CAYMAN - Simamora, Bene Fetresya; Pahlawan, Indra (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This study will examine how the role of OECD as an international organization dealing with issues of international economic development in addressing international tax evasion through tax havens countries. Tax haven is a phenomenon where there is a regulation that implements a system of taxation which is not in accordance with international taxation. One of the countries grouped in the state of tax havens by OECD is Cayman Island. Many countries want to attract investors into the country and carried out by the Cayman Island by applying zero tax system.For a country that is not a tax haven countries this problem is a very serious problem. This study uses library research where data taken from all sources relevant to the research problem. This study uses the level of analysis of international organizations and using the theory of the role of international organizations and the theory put forward by Clive Archer.This study shows that the OECD as an international organization in the economic development of the world to take concrete steps in addressing the issues of international tax evasion through tax haven countries especially those in the Cayman Island by applying a Tax Information Exchange Agreements and the OECD rules is followed by the Cayman Islands countries as a step to avoid international tax evasion .Keywords : International Organization, Role and International Organization Theory, Tax Haven, Tax Haven Country, Cayman Island, Tax Information Exchange Agreements, Tax Evasion, OECD.